2021
DOI: 10.1038/s41598-021-82127-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-stress analysis of a damaged solid sphere using hyperbolic two-temperature generalized thermoelasticity theory

Abstract: This work aims to study the influence of the rotation on a thermoelastic solid sphere in the context of the hyperbolic two-temperature generalized thermoelasticity theory based on the mechanical damage consideration. Therefore, a mathematical model of thermoelastic, homogenous, and isotropic solid sphere with a rotation based on the mechanical damage definition has been constructed. The governing equations have been written in the context of hyperbolic two-temperature generalized thermoelasticity theory. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…As a result, they modified the two-temperature model to the hyperbolic twotemperature model, in which the difference between the second derivative concerning the time of the dynamical and conductive temperature is proportional to the heat supply, and found that this model introduces a thermal wave that propagates with a limited speed. Recently, [22][23][24] discussed different types of problems in the context of the HTT theory of thermoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they modified the two-temperature model to the hyperbolic twotemperature model, in which the difference between the second derivative concerning the time of the dynamical and conductive temperature is proportional to the heat supply, and found that this model introduces a thermal wave that propagates with a limited speed. Recently, [22][23][24] discussed different types of problems in the context of the HTT theory of thermoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar and Sharma (2021b) studied the impact of two-temperature in a piezothermoelastic medium with fractional order derivative. Further, considering the accelerating thermal and conductive temperatures, Youssef and Bary (Youssef and El-Bary, 2018) discovered the new hyperbolic-two-temperature (HTT) model updated the CTT model and found a way to address the paradox of thermal wave propagation at infinite speed. Bassiouny and Rajagopalan (2020), Bassiouny (2021) and Hobiny et al (2022) investigated the different thermoelastic models in the framework of the HTT theory.…”
Section: Introductionmentioning
confidence: 99%
“…Youssef (2006) expanded the field equations of thermoelasticity by incorporating the thermal relaxation parameter, developing the generalized theory of two temperatures. Furthermore, addressing the paradoxical phenomenon of thermal wave propagation occurring at an infinite speed, Youssef and El-Bary (2018) introduced a new model called the hyperbolic-two-temperature (HTT), which pertains to the phenomenon of accelerating conductive and thermal temperatures. Hobiny et al (2022) conducted a comprehensive exploration of various thermoelastic models, analyzing their characteristics and behavior under the HTT framework.…”
Section: Introductionmentioning
confidence: 99%